Market Access and Performance (MAP) Study; Technical and Governing Barriers to Trade in the Central Asian Region (CAR) (Case Study on Trade in Apricots) (Salam International Academic Journal, 2022)
This paper assesses non-tariff barriers to trade in the above-mentioned countries from two perspectives: the first is MAP; procedural and regulatory barriers to trade, both inside the region and with countries outside of the region; while the second perspective looks at a concrete example by focusing on the export of apricots (fresh and dried). Apricots were selected for this case study because they are produced in all of the CAR countries, although the growing conditions and volumes are different, as is their export potential.     The preparation of this paper involved: (a) desk research to review the work undertaken by international organizations, donor agencies, and trade associations on Technical and Governing Barriers to Trade in the Central Asian Region (CAR) Region, including apricots, (b) the identification of 27 respondents including 18 companies, involved in export/import, and 9 export promotion organizations, private business associations, foreign countries’ trade representatives and experts in the CAR region, and other countries active in the region (Russia, Turkey), and (c) telephone and online interviews using two types of questionnaires made up of 5-8 questions. The first questionnaire was focused on general procedural and regulatory barriers to trade; the second dealt specifically with procedural and regulatory barriers to trade in fresh and dried apricots.
Keywords: Trade Barriers; Non-Tariff, Market Access & Performance; Technical and Governing